Environmental and Ergonomic Determinants of Musculoskeletal Disorders (MSDs) Among Oil Palm Harvesters: A Literature Review - Ayie Damayanti; Adian Khoironi; MG Catur Yuantari; Supriyono Asfawi (Journal of Bioresources and Environmental Sciences, 2026)
The oil palm plantation industry continues to expand rapidly, positioning Indonesia as the world’s largest producer, followed by Malaysia and Thailand. However, this growth is accompanied by a rising prevalence of musculoskeletal disorders (MSDs) among oil palm farmers, primarily due to heavy physical workloads and non-ergonomic postures during harvesting activities. A systematic search was conducted using PubMed, ScienceDirect, ResearchGate, and Google Scholar to identify studies published between 2020 and 2025 that examined MSD complaints, ergonomic risk factors, and work postures among oil palm workers. Nine articles met the inclusion criteria and were analyzed. The findings show that the most common MSD complaints occur in the neck, shoulders, wrists, lower back, feet, and knees. These issues arise mainly from manual harvesting tasks, such as cutting fronds and fresh fruit bunches (FFB) using egrek and dodos tools, as well as transporting harvested fruit. Key risk factors include awkward postures, repetitive movements, long working hours, heavy physical loads, age, and years of service. Beyond individual ergonomic factors, the studies reviewed highlight the significant impact of environmental conditions uneven terrain, slippery soil, extreme heat, dense vegetation, and varying land contours which increase biomechanical stress and force workers into compensatory postures, elevating MSDs risk. The interaction between tool design and challenging field conditions underscores that ergonomics and environmental management are closely interconnected. Recent advances in wearable technologies, including Electromyography (EMG) and Inertial Measurement Units (IMU), offer more accurate real-time assessments of posture, muscle activity, and environmental influences, supporting data-driven prevention strategies. While mechanical harvesting tools show potential to reduce MSD risk, their success depends on ergonomic design, field adaptability, and worker acceptance. Recommendations include designing environment-sensitive ergonomic tools, improving field accessibility, providing training on safe techniques, and implementing early sensor-assisted health monitoring.